SELF HELP GROUPS IN INDIA AS INSTRUMENTS FOR POVERTY ALLEVIATION: A COMPARATIVE ANALYSIS OF URBAN AND RURAL INITIATIVES - Bhise, Anita Dasharath Gorkhe; Srinivas, Vijayalakshmi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Self Help Groups (SHGs) have emerged as powerful tools for poverty alleviation in India, providing financial independence and social empowerment to marginalized communities. This paper presents a comparative analysis of SHGs in urban and rural areas, examining their impact on poverty reduction, income generation, and women’s empowerment. While both urban and rural SHGs share common objectives—such as fostering savings, improving access to credit, and promoting entrepreneurship—their methods, challenges, and outcomes differ significantly due to varying socio-economic environments. In rural areas, SHGs primarily focus on agriculture, traditional livelihoods, and small-scale industries, playing a crucial role in addressing seasonal income fluctuations and access to resources. In contrast, urban SHGs emphasize entrepreneurial ventures, services, and non-agricultural sectors, facing challenges like migration, higher living costs, and competitive markets. This study analyzes case studies of SHGs from diverse geographical locations, utilizing both primary and secondary data to assess their economic and social impacts. The findings suggest that while rural SHGs are effective in strengthening community cohesion and supporting agricultural activities, urban SHGs demonstrate higher levels of innovation and financial inclusion. Both contexts, however, highlight the critical role of SHGs in women’s empowerment, enabling greater participation in household decision-making and leadership roles. Policy recommendations include enhancing government support tailored to the unique needs of urban and rural SHGs, fostering sustainability, and addressing specific challenges in each context. The study concludes that SHGs, when supported adequately, have the potential to be transformative agents for poverty alleviation across India’s diverse landscapes.